Reconfigurable multiband tapered slot antenna - Chagharvand, Sahar (John Wiley and Sons Inc., 2015)
In this article, a reconfigurable multiband tapered slot antenna is proposed. This antenna is able to support wideband, dual-band, and triple-band operations. This is achieved by incorporating T- and C- shaped resonators that are used to integrate a filtering functionality to the antenna. The behavior of the antenna can be reconfigured by activating/deactivating the different resonators by means of PIN diode switches. By activating only the T-shaped resonator, a bandstop operation is obtained which results in a dual-band operation, while by coupling both T- and C-shaped resonators, a triple-band operation is achieved. By deactivating all of the resonators, a wideband operation is achieved. Results show, the frequency range of the wideband operation spans from 1.04 to 3.76 GHz. In the dual-band operation mode, the suppressed band is around 2.5 GHz. The operating frequency range of the triple-band operation is divided into low frequency (0.97-1.24 GHz), midfrequency (1.63-2.08 GHz), and high frequency (2.64-3.71 GHz) bands. To validate the proposed approach both simulated and measured results are given and a good agreement is observed.